Analisis Nilai Estetika dan Makna Visual Karya Pemenang Lomba Desain Batik Kota Tangerang Selatan 2023 - Fariz Al Hazmi (Telkom University, 2024)
The process of designing motifs is one of the stages in making batik work before processing. This process requires creativity and knowledge in making something into a motif. In the batik design competition held by the City of South Tangerang in 2023, one work was won with the title